Diseño de la Finca Agroturística Armenia, mediante la elaboración del plan de negocios para fortalecer el agroturismo en el Cantón Francisco de Orellana, provincia de Orellana - Guevara Paz, Carmen Luiza (2018)
Ecuador is considered a mega diverse, floricultural and multiethnic country because it has a scenic wealth, natural, cultural, and historical resource cataloged unique worldwide; that should be exploited by the Amazonian Kichwa communities, through the creation of micro tourism ventures, offering quality products and services. In the country tourism has been described as a strategic axis to achieve economic development through the implementation of strategies, policies and programs aimed at diversifying the supply of tourism services through the Plan of Good Living. Likewise, the Armenian parish has most visited tourist attractions, rural parishes of the canton Francisco de Orellana, also has an unparalleled scenic beauty. Which are not used to produce income for the benefit of the local population. Therefore, it is important to take advantage of knowledge in natural and cultural productive activities. For the realization of the project was established as a general objective of the research: Design the farm "Armenia" through the development of a business plan to disseminate the agrotourism, in the Armenian parish, canton Francisco de Orellana, province of Orellana; Three specific objectives derive from it, the first was focused on Situational diagnosis of the study area of the agro-turistic farm "Armenia"; the second proposes the business plan of the agrotourism farm "Armenia"; the third one to carry out the socialization of the studies of the agro-turistic farm "Armenia". To improve the development of the project and achieve establish the specific objectives of the research using appropriate methods and techniques. In the first objective, the inductive, statistical and descriptive methods were used, obtaining general data and visualizing the internal and external reality of the study area. With regard to techniques that were used, the survey was the same that after a sampling was directed to 384 people, allowing to know the needs and preferences of the market. Inventory cards and ranking of tourist attractions established by the Ministry of Tourism were used. In the second objective, the deductive and inductive methods were applied, which were used to simplify the information. In the financial study, evaluation criteria are indicated, where a Net Present Value of $ 81,372.13 was obtained, an Internal Rate of Return of 30.76%; the Benefit-Cost relationship indicated that for each dollar invested, one gets $ 0.28 cents of utility dollars, and one Capital Recovery Period of 2 years, 6 months and 4 days; The third objective, allowed to present the proposal of the investigative work directly to the staff of the farm and authorities of the parish, as a result of the socialization it was determined that the proposal is a very attractive business idea that will contribute to local tourism development. After the work done, it is concluded that the "Armenia" farm is well received, viable and profitable. Therefore, the owner is recommended to execute it.